A Graphical Tool Designed to Deploy Wireless Sensors in Homogeneous Grid Selected from Irregular Polygon - Nitin, DR. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
In this paper, we present a graphical tool, which will help us with algorithms that are used for finding Quality of Service. This tool relates these algorithms to the real world and thus provides a better insight into the actual problems of deploying sensors in a field and finding out whether QoS would be achieved or not. We have used Mathematical Gur Game and its application to deploy the sensors in the homogeneous are, which is selected from the Irregular Polygon.